Reproduksi Otoritas Keagamaan di Pesantren Daaru Attauhid Muaro Kumpeh: Pendidikan Berbasis Tauhid dan Respon Masyarakat - Mesalina, Juliana; Zahara, Anzu Elvia; Kusnadi, Edy; Rafii, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article stems from anxiety about religious authority which is unstable and difficult to control in the religious sector specifically in Indonesia. This article will explore how the Daaru Attauhid Islamic boarding school reproduces religious authority through monotheism-based education. This research uses a phenomenological approach in answering these questions in order to obtain in-depth meaning. This article finds that special education is given to students who want to graduate from Islamic boarding schools, especially the books of Siyarus Salikin, Fathur Rabbani, and al-Hikam. Apart from limited discussions, students are ordered to attend recitations which are open to the public, namely attended by the majority of the public. The public's response to the recitation, both general and specific, was considered positive, namely education in depth and limited to certain students. The conclusion of this article is that the reproduction of religious authority at the Daaru Attauhid Islamic Boarding School has the potential to become a legacy for the students that will spread to the public. This authority can at least be obtained through a deep understanding of the science of monotheism.